Lightweight Cement-Based Composites Incorporating Hollow Glass Microspheres: Fresh and Hardened State Properties - Kabay, Nihat; Kizilkanat, Ahmet B.; Akturk, Busra; Kahraman, Yusuf (TURKISH CHAMBER CIVIL ENGINEERS, 2022)
This research aims to develop a lightweight cementitious composite with satisfying mechanical and good thermal insulating properties. Two different types of hollow glass microspheres (HGM) were used as lightweight aggregates and were substituted with fine aggregate by 10, 20, and 40% by volume. The rheological, physical, mechanical, and microstructural properties of the resulting HGM-incorporated composites were investigated and correlations were established between physical and mechanical test results. The results showed that the physical and mechanical properties of individual HGM particles play a dominant role in the properties of lightweight mortars. HGM addition provided reductions up to 20% in the density and 45% in the thermal conductivity values of mortars compared to the reference. The best HGM ratio in the tested range was found as 20%, which provides benefits such as reduced density and enhanced thermal insulation capability without causing a significant reduction in compressive strength. It was concluded that HGMs can be used in the lightweight cementitious mortar production which has great potential in building applications to reduce the heating energy consumption.
Keywords: Hollow glass microspheres; rheology; mechanical properties; thermal conductivity; microstructure; MECHANICAL-PROPERTIES; FLY-ASH; YIELD-STRESS; THERMAL-CONDUCTIVITY; EXPANDED PERLITE; CONCRETE; STRENGTH; AGGREGATE; SIZE; Engineering